Spatial and institutional analysis of the voivodships expenditure on culture in the years 2003 - 2015 - Adam Mateusz Suchecki (e-Finanse: Financial Internet Quarterly, 2019)
Following the completion of the process of decentralisation of public administration in Poland in 2003, a number of tasks implemented previously by the state authorities were transferred to the local level. One of the most significant changes to the financing and management methods of the local authorities was the transfer of tasks related to culture and national heritage to the set of tasks implemented by local governments. As a result of the decentralisation process, the local government units in Poland were given significant autonomy in determining the purposes of their budgetary expenditures on culture. At the same time, they were obliged to cover these expenses from their own revenues. This paper focuses on the analysis of expenditures on culture covered by the voivodship budgets, taking into consideration the structure of cultural institutions by their types, between 2003-2015. The location quotient (LQ) was applied to two selected years (2006 and 2015) to illustrate the diversity of expenditures on culture in individual voivodships.
Keywords: H7; Z1; 330; expenses on culture; voivodships budgets; local finances; cultural institutions; location quotient